A limit theorem of nonlinear filtering for multiscale McKean–Vlasov stochastic systems - Qiao, Huijie; Zhu, Shengqing (Comptes Rendus. Mathématique)
The work concerns about multiscale McKean–Vlasov stochastic systems. First of all, we prove an average principle for these systems in the $L^2$ sense. Moreover, a convergence rate is presented. Then we define the nonlinear filtering of these systems and establish a limit theorem about nonlinear filtering of them in the $L^2$ sense.